How Does Language Change Perception: A Cautionary Note - Klemfuss, Nola; Prinzmetal, Bill; Ivry, Richard B. (Frontiers in Psychology, 2012)
The relationship of language, perception, and action has been the focus of recent studies exploring the representation of conceptual knowledge. A substantial literature has emerged, providing ample demonstrations of the intimate relationship between language and perception. The appropriate characterization of these interactions remains an important challenge. Recent evidence involving visual search tasks has led to the hypothesis that top-down input from linguistic representations may sharpen visual feature detectors, suggesting a direct influence of language on early visual perception. We present two experiments to explore this hypothesis. Experiment 1 demonstrates that the benefits of linguistic priming in visual search may arise from a reduction in the demands on working memory. Experiment 2 presents a situation in which visual search performance is disrupted by the automatic activation of irrelevant linguistic representations, a result consistent with the idea that linguistic and sensory representations interact at a late, response-selection stage of processing. These results raise a cautionary note: While language can influence performance on a visual search, the influence need not arise from a change in perception per se.